Penerapan Teknik Relaksasi Guide Imagery terhadap Penurunan Nyeri Epigastrium pada Pasien Gastritis di Sukoharjo - Kurniawan Trikuncoro; Hermawati Hermawati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Gastritis is a disease that is often found in the general public, this disease affects all walks of life according to the World Health Organization. The incidence of gastritis in the world is around 1.8-2.1 million of the total population each year. According to data obtained from the Weru Health Center ranks 10th out of 20 major diseases at the Weru Health Center, reaching 149 cases. Guide Imagery is one of the pain distraction techniques aimed at handling pain, lowering blood pressure, relieving anxiety. One group pre test and post design method, the subjects in this research case study were 2 respondents who experienced gastritis, 1 application of guide imagery was carried out for 3 days with a duration of 15 minutes. After the guide imagery technique, 1 application for 3 days, both respondents experienced a decrease in the epigastric pain scale from a moderate pain scale to a mild pain scale, Mrs. S from scale 5 to 2 and Mrs. M from scale 4 to 1. Guide imagery is very effective for reducing epigastric pain in gastritis patients.